2021
DOI: 10.3390/app11083550
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Mix Proportions on Rheological Properties, Air Content of Wet Shotcrete—A Case Study

Abstract: To study the influence of different mix proportions on the fresh properties of wet shotcrete, the rheological properties and air content of wet shotcrete with different admixtures before pumping were measured. In addition, the pressure drop along the pipeline and the build-up thickness were studied, and the relationship between the rheological properties and the pumpability and sprayability was discussed. This paper attempts to reveal the influence mechanism of admixtures on the fluidity of wet shotcrete by me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Another contributing factor to the increased flow is the ball-bearing effect of fine bubbles smaller than 450 μm . It is postulated that a high number of these fine bubbles can act as a cushion between particles and aggregates to reduce the internal friction of the paste or concrete and increase the flow of the system. , As will be discussed in the next section, proteins result in many very fine bubbles that can lead to ball-bearing interactions. Although this phenomenon is more significant in mortar and concrete where aggregates with irregular shapes and pointy corners are present, it still affects the flow of cement particles in the paste.…”
Section: Resultsmentioning
confidence: 99%
“…Another contributing factor to the increased flow is the ball-bearing effect of fine bubbles smaller than 450 μm . It is postulated that a high number of these fine bubbles can act as a cushion between particles and aggregates to reduce the internal friction of the paste or concrete and increase the flow of the system. , As will be discussed in the next section, proteins result in many very fine bubbles that can lead to ball-bearing interactions. Although this phenomenon is more significant in mortar and concrete where aggregates with irregular shapes and pointy corners are present, it still affects the flow of cement particles in the paste.…”
Section: Resultsmentioning
confidence: 99%
“…This Special Issue has published nine papers (eight research papers and one review paper) covering many fields of advanced support technology, including support materials, disaster prevention of surrounding rock damage, deterioration of support structure, pipeline pumping, and road traffic. Xie et al [9] reported the influence of different additives on the fresh performance of wet-shotcrete, finding that free grout effect and ball effect would significantly affect the performance of wet-shotcrete. The authors discussed the relationship between rheological characteristics and pumpability and spraying ability, and finally put forward suggestions for a mixing ratio meeting the requirements of various shotcrete.…”
mentioning
confidence: 99%